Tuan Guru Kyai Haji Muhammad Zainuddin Abdul Madjid’s Leadership in Development of Nahdlatul Wathan School in West South East Nusa (A Qualitative Study on Phenomenology) - Nasruji , Rahman Hasibuan , Hazriyanto (International Journal of Advanced Science and Technology, 2020)
Madrasah Nahdlatul Wathans (NW) was built by Kyai Muhammad Zainuddin Abdul Madjid (Hamzanwadi) and then he succeeded in developing this school to be more than 800 schools in late of his life. These schools spread not only in Western South East Nusa, but also other areas in Indonesia. This study tried to analyze the settings that made him did so. This study was conducted by using qualitative approach on phenomenology point of view. There were 51 informants that were involved in this study and 2 of them were appointed as key informants. The results of the study show that: (a) Hamzanwadi’s success in developing the school of NW because of his vision that concern on human goodness and he committed to realize that vision until his death; (b) the strategy that he chose to reach his vision was varied and across many sectors; and (c) the management patterns that he developed was planned carefully, but he failed to unite the schools in its operation.This study concluded that Hamzanwadi’s success because of his great vision and it implies that a great leader must have a great vision.